THE MODEL OF THE KUMON LEARNING MODEL ON STUDENT LEARNING OUTCOMES ON THE SUBJECT MATTER OF NORMA CLASS VII SEMESTER II SMP DHARMA BAKTI MEDAN - Minar Trisnawati Tobing (Jurnal Ilmiah Teunuleh, 2020)
This study aims to determine the significant effect of the Kumon learning model on Civics learning outcomes on the subject matter of norms. This type of research is a quasi-experimental (quasi-experimental). The population in this study were all class VII SMP Dharma Bakti Medan as many as 2 classes, each class consisting of 30 people. The sample of this study was taken from the population, by means of (cluster random sampling), namely class VII-1 as the experimental class which is taught by the Kumon learning model and class VII-2 as the control class which is taught by the direct learning model. The instrument used in this study was a multiple-choice test with a total of 20 items with 4 options (a, b, c, d) which had previously been tested at a higher class to determine the validity, reliability, level of difficulty and discriminating power of the questions. The results showed, at the end of the study, a post-test was carried out, the average score was obtained 73,33 with standard deviation 10,449 and the control class obtained the average value 62,16 with standard deviation 11,647. The results of the statistical test (ttest) obtained the price tcount = 4,59 dan ttable = 1,67 because tcount < ttable, This shows that there is a significant effect of the Kumon Learning Model on Civics Learning Outcomes on the subject matter of Norms in Class VII SMP Dharma Bakti Medan.